Microcystis aeruginosa removal by the combination of ultrasound and TiO2/biochar. Issue 40 (19th July 2021) - Wang, JuanJuan; Li, Wenshu; Wu, Xiaoge
Abstract : Ultrasound irradiation was combined with TiO2 /biochar (TiO2 /BC) at relatively low dosage to promote the coagulation of Microcystis aeruginosa . Abstract : Harmful cyanobacteria blooms are increasing. They call for novel removal technology, since the required doses of algaecides may cause further environmental pollution or damage treatment facilities. Undesirable intracellular compounds can be released in the water when cyanobacterial cells are damaged. For the first time, ultrasound irradiation was combined with TiO2 /biochar (TiO2 /BC) at relatively low dosage and tested as an alternative for promoting the coagulation of Microcystis aeruginosa in water treatment. This pre-oxidation process removed 92% of cyanobacterial cells after coagulation. With the combination of ultrasound and TiO2 /BC treatment, the dissolved organic carbon and microcystins levels did not increase significantly. The oxidative treatments enhanced the permeability of the cyanobacterial cell membranes, which may be due to the various active species generated from the ultrasound and TiO2 /BC process. The results showed that the TiO2 /BC hybrid catalyst could be a potential candidate for cyanobacterial cells removal in water.